Ecological anatomy of wood from Guarea kunthiana A. Juss. (Meliaceae) - Baldin, Talita; Nunes, Sâmara Magdalene Vieira; Santos, Emmyle Katterine Souza; Dias, Thalles Loiola; Barauna, Edy Eime Pereira; Nisgoski, Silvana (Scientia Agraria Paranaensis, 2022)
Light and water availability are determining factors for variations in the anatomical and morphological characteristics of wood. In view of the above, the aim of this work was to carry out an anatomical-ecological analysis of the wood and leaf morphology of Guarea kunthiana A. Juss. (Meliaceae), occurring in the Cavernas do Peruaçu National Park (MG), to understand the plant-environment interactions and how these interactions affect the anatomical characteristics of the wood. For this purpose, three trees were selected considering the difference in botanical patterns of leaves and tree size, the distance to the watercourse that enters the cave and the incidence of light on them. Wood was collected from each sample nondestructively at DAP, from leaves at random heights and from light intensity. Anatomical characterization was then carried out using histological and macerate slides. To compare the morphological aspects of the leaves, the blade length, blade width, length/width ratio and blade area (A²) were determined. All characters were correlated using Spearman analysis to verify the influence of the environment on wood anatomy. The anatomical components found are common to the genus and family; proximity to watercourses has a greater influence on the number of anatomical elements than does light intensity. There is a strong association between leaf blade area and wood anatomy. It is concluded that the G. Kunthiana has anatomical adaptations for mesomorphic environments.